Evaluación de pretratamientos químicos para la hidrólisis enzimática de residuos lignocelulósicos de yuca (Manihot esculenta Crantz) (2013)
ABSTRACT: The effect of different chemical pretreatment with sulfuric acid (H2SO4), sodium hydroxide (NaOH) and hydrogen peroxide (H2O2) were evaluated by quantifying total reducing sugars produced during enzymatic hydrolysis step of lignocellulosic residues cassava (Manihot esculenta Crantz) and lignin removal percentage after pretreatment. The amount of waste used (1 to 5%) (w/v) in different particle sizes (1.18 and 0.6 mm) were pretreated separately (leaves and stems) with H2SO4, NaOH and H2O2 at varying concentrations (1 and 5%) (w/v). Plant residues were hydrolyzed with enzyme Accellerase 1500 with 50 ° C, pH 5 and 140 rpm. NaOH pretreatment enables higher total reducing sugars released during enzymatic hydrolysis (3.7 g/L) followed by leave pretreatments using H2SO4 (2.11 g/L) and H2O2 (1.54 g/L). Sugar concentrations were lower in stem pretreatments.